Growth hormone releasing peptide-6 (GHRP-6) prevents doxorubicin-induced myocardial and extra-myocardial damages by activating prosurvival mechanisms - Berlanga-Acosta, Jorge; Cibrian, Danay; Valiente-Mustelier, Juan; Suárez-Alba, José; García-Ojalvo, Ariana; Falcón-Cama, Viviana; Jiang, Baohong; Wang, Linlin; Guillén-Nieto, Gerardo (Frontiers in Pharmacology, 2024)
Dilated cardiomyopathy (DCM) is a fatal myocardial condition with ventricular structural changes and functional deficits, leading to systolic dysfunction and heart failure (HF). DCM is a frequent complication in oncologic patients receiving Doxorubicin (Dox). Dox is a highly cardiotoxic drug, whereas its damaging spectrum affects most of the organs by multiple pathogenic cascades. Experimentally reproduced DCM/HF through Dox administrations has shed light on the pathogenic drivers of cardiotoxicity. Growth hormone (GH) releasing peptide 6 (GHRP-6) is a GH secretagogue with expanding and promising cardioprotective pharmacological properties. Here we examined whether GHRP-6 administration concomitant to Dox prevented the onset of DCM/HF and multiple organs damages in otherwise healthy rats.Myocardial changes were sequentially evaluated by transthoracic echocardiography. Autopsy was conducted at the end of the administration period when ventricular dilation was established. Semiquantitative histopathologic study included heart and other internal organs samples. Myocardial tissue fragments were also addressed for electron microscopy study, and characterization of the transcriptional expression ratio between Bcl-2 and Bax. Serum samples were destined for REDOX system balance assessment. GHRP-6 administration in parallel to Dox prevented myocardial fibers consumption and ventricular dilation, accounting for an effective preservation of the LV systolic function. Dox also attenuated extracardiac toxicity preserving epithelial organs integrity, inhibiting interstitial fibrosis, and ultimately reducing morbidity and mortality. Mechanistically, GHRP-6 proved to sustain cellular antioxidant defense, upregulate prosurvival gene Bcl-2, and preserve cardiomyocyte mitochondrial integrity. These evidences contribute to pave potential avenues for the clinical use of GHRP-6 in Dox-treated subjects.